Six-methoxyflavone suppresses CircPIAS1 biogenesis via targeting PTBP1 and, in combination with IFN-γ, promotes ferroptosis in melanoma - Guo, Yong-Qi; Wu, Xi; Zang, Xin; Liu, Cheng-Yan; Wang, Meng-Yue; Xiao, Cheng-Mei; Hou, Hui; Zhang, Li-Fang; Xia, Yuan-Zheng; Kong, Ling-Yi (Frontiers in Pharmacology, 2025)
Background/ObjectivesMelanoma remains a highly aggressive malignancy with limited therapeutic options targeting its underlying pathogenesis. CircPIAS1 (circbase ID: hsa_circ_0008378) and its encoded protein circPIAS1-108aa contribute to tumor progression by suppressing STAT1 phosphorylation and immunogenic ferroptosis, yet specific pharmacological agents of directly targeting circPIAS1 are lacking. This study aimed to identify natural products that selectively inhibit circPIAS1 biogenesis, there-by exploring novel therapeutic strategies for melanoma.MethodsA library of 128 anticancer natural products was screened using qRT-PCR to identify metabolites selectively suppressing circPIAS1, with 6-methoxyflavone (6-MF) selected. CCK-8 assay determined 6-MF’s IC50 for inhibiting melanoma cell proliferation. RNA sequencing and western blot analyzed the PI3K-AKT pathway, STAT1 phosphorylation, SLC7A11/GPX4 signaling pathway, and circPIAS1-108aa. EdU and lipid ROS assays evaluated cell proliferation and oxidative response. RBPmap database identified PTBP1 as a key RNA-binding protein (RBP) in circPIAS1 biogenesis, validated via dose/time-dependent 6-MF treatments and siRNA experiments. A subcutaneous tumor model was used to evaluate the effects of 6-MF, a PD-1 inhibitor, and their combination.Results6-MF was identified as a selective suppressor of circPIAS1 without affecting its host PIAS1 gene. Mechanistically, 6-MF inhibited PTBP1 (critical for circPIAS1 biogenesis) in a dose- and time-dependent manner, reducing circPIAS1-108aa expression. It suppressed the PI3K-AKT pathway,and when combined with IFN-γ, it significantly enhanced STAT1 phosphorylation, and downregulated SLC7A11/GPX4, increasing lipid ROS and promoting ferroptosis. In vivo, 6-MF combined with PD-1 inhibitor synergistically inhibited melanoma growth.Conclusion6-MF targets PTBP1 to inhibit circPIAS1 biogenesis and reduce circPIAS1-108aa.6-MF inhibits PI3K-AKT pathway; combined with IFN-γ, it enhances STAT1 phosphorylation, inhibits SLC7A11/GPX4 pathway, promoting melanoma ferroptosis. Its combination with PD-1 inhibitor enhances antitumor efficacy, providing a novel therapeutic strategy for melanoma treatment.